2017
DOI: 10.1016/j.cjtee.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality, hospital length of stay and need for surgery in pediatric trauma patients

Abstract: PurposePediatric trauma is one of the major health problems around the world which threats the life of children. The survival of injured children depends upon appropriate care, accurate triage and effective emergent surgery. The objective of this study was to determine the predictive values of injury severity score (ISS), new injury severity score (NISS) and revised trauma score (RTS) on children's mortality, hospitalization and need for surgery.MethodsIn this study, records of trauma patients under 15 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
3
10
0
1
Order By: Relevance
“…As for secondary outcomes, all three trauma scores demonstrated a linear correlation with hospital length of stay after adjusting for age, gender, and trauma mechanism (Table 4). This result was similar to a previous study in China that showed that increased ISS and decreased RTS were correlated with an increased length of hospital stay [38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As for secondary outcomes, all three trauma scores demonstrated a linear correlation with hospital length of stay after adjusting for age, gender, and trauma mechanism (Table 4). This result was similar to a previous study in China that showed that increased ISS and decreased RTS were correlated with an increased length of hospital stay [38].…”
Section: Discussionsupporting
confidence: 92%
“…The cutoff values selected from the ROC analysis of ISS, GCS, and RTS were 15, 11, and 7, respectively. A similar cutoff value for ISS was reported in a previous study by Yousefzadeh Chabok et al [38]. Both the sensitivity and specificity for mortality prediction regarding the selected cutoff values from each trauma score system were high (Table 5).…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we present retrospectively analyzed data from a total of 88 cases of pediatric PT admitted to our level 1 trauma center. Epidemiological exploration revealed road traffic-associated accidents as the most frequent type of accident in our study population followed by falls from large height, similar to findings from previous publications on pediatric PT (3, 6, 18). A significant association of the incidence of thorax trauma and lung contusions with the stratified ISS was found.…”
Section: Discussionsupporting
confidence: 90%
“…). Following assessment, 68 articles, involving 708 032 patients across 71 LMICs, were included in the review ( Tables S1 and S2 , supporting information). Country‐specific patient numbers were reported in 60 studies but were absent from six and two provided total LMIC patient numbers only.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes following cancer surgery were common topics, including breast, gastric, colorectal and prostate cancer, and hepatocellular carcinoma. Cardiac surgery, caesarean section and genitourinary fistula were also well represented in included articles, whereas clinical presentations included burn management, trauma, appendicitis, groin hernias and orthopaedic fracture management.…”
Section: Resultsmentioning
confidence: 99%